Nyāya siddhānta dīpaḥ of Śaśadhara: (containing the text, Eng. translation, and critical study of the first five Vādas - Dalai, B. K. (Pratibha Prakashan, 2005)
Study of Nyāyasiddhāntadīpa of Śaśadhara, treatise on Nyaya philosophy; includes Sanskrit text with English translation.